1986
DOI: 10.1126/science.234.4783.1509
|View full text |Cite
|
Sign up to set email alerts
|

Advent and Course of Pastoralism in the Kalahari

Abstract: It has long been thought that farming and herding were comparatively recent introductions into the Kalahari and that it has been a preserve of foraging "Bushmen" for thousands of years. Agropastoral Bantu-speakers were thought to have entered this region only within the last two centuries. However, fully developed pastoralism and metallurgy are now shown to have been established in the Kalahari from A.D. 500, with extensive grain agriculture and intracontinental trade added by A.D. 800. Archeological, linguist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 12 publications
2
32
0
1
Order By: Relevance
“…Inorganic ®xation of PO 4 -P could occur because of the relatively high Fe and Ca concentrations of Kalahari soils (Table I). Such inorganic ®xation of phosphate in Kalahari soils would suggest that changes in total P distribution in soils would be long lived, as redistribution mechanisms, such as through plant root systems, act principally through plant-available PO 4 -P. The longevity of P enrichment in soils is a factor that has been noted in previous studies investigating spatial patterns of P in southern African soils (Denbow and Wilmsen, 1986;Blackmore et al, 1990). Such ®ndings suggest that whilst grazing will cause signi®cant increases in total P concentrations in intensively grazed areas, dung additions are unlikely to increase inorganic P availability.…”
Section: Discussionmentioning
confidence: 88%
“…Inorganic ®xation of PO 4 -P could occur because of the relatively high Fe and Ca concentrations of Kalahari soils (Table I). Such inorganic ®xation of phosphate in Kalahari soils would suggest that changes in total P distribution in soils would be long lived, as redistribution mechanisms, such as through plant root systems, act principally through plant-available PO 4 -P. The longevity of P enrichment in soils is a factor that has been noted in previous studies investigating spatial patterns of P in southern African soils (Denbow and Wilmsen, 1986;Blackmore et al, 1990). Such ®ndings suggest that whilst grazing will cause signi®cant increases in total P concentrations in intensively grazed areas, dung additions are unlikely to increase inorganic P availability.…”
Section: Discussionmentioning
confidence: 88%
“…Lee 1979). The 'revisionists', such as Denbow and Wilmsen ( 1986), criticised this perspective. They held that Bushmen groups had been in constant exchange with Bantu people, and that historical processes had led to the Bushmen's marginalisation, making them 'increasingly dependent on welfare and tourist handouts' (Wilmsen 1990: 140).…”
Section: Perceptions Of Bushmenmentioning
confidence: 99%
“…In fact, Tsodilo became the site as the basis or the inspiration for the development of the argument that our understandings about the lifeways and histories of hunter-gatherers must be revised, thus instigating the so-called Kalahari Debate, which is discussed in chapter 4. For example, James Denbow and Edwin Wilmsen argued that archaeological evidence at Tsodilo showed that hunter-gatherers (Khoisan speakers) and pastoralists (Bantu speakers) had interacted for several hundred years (Denbow and Wilmsen 1986). Thus the researchers attempted to dispel the notion that Khoisan speakers occupied the Kalahari alone-and in an imagined utopian, "un-contacted" state-until a more recent arrival by Bantu speakers.…”
Section: Researching Tsodilomentioning
confidence: 99%
“…On the other side of the debate, the "revisionists" argued that Khoisan speakers had adapted their subsistence strategies when in contact with other ethnic groups prior to European contact and were not purely hunting and gathering throughout time (Wilmsen 1989(Wilmsen , 1993Wilmsen and Denbow 1990). Revisionists, basing most of their work on archaeological and ethnohistoric accounts in Botswana (Tsodilo is a pivotal site to their claims), scoffed at the traditionalists' idealist view, and pushed forth the notion of a much more complex settlement of the Kalahari and surrounds (Schrire 1980, Denbow and Wilmsen 1986, Wilmsen 1989. Edwin ("Ed") Wilmsen, a key proponent of the revisionist argument, advocated the move away from considering Khoisan speakers as ethnically distinctive and toward analyzing them from a Marxist perspective as a proletariat class (Wilmsen 2002).…”
Section: Ethnicity In the Pastmentioning
confidence: 99%